A Novel Melt Processing for Mg Matrix Composites Reinforced by Multiwalled Carbon Nanotubes. Issue 12 (December 2016) - Shi, H.L.; Wang, X.J.; Zhang, C.L.; Li, C.D.; Ding, C.; Wu, K.; Hu, X.S.
Abstract : Carbon nanotubes (CNTs) reinforced Mg matrix composites were fabricated by a novel melt processing. The novel processing consisted of two courses: CNTs pre-dispersion and ultrasonic melt processing. Mechanical ball-milling was employed to pre-disperse CNTs on Zinc (Zn) flakes. Serious CNT entanglements were well dispersed to single CNT or tiny clusters on Zn flakes. The ultrasonic melt processing further dispersed CNTs in the Mg melt, especially tiny CNT clusters. Thus, a uniform dispersion of CNTs was achieved in the as-cast composites. Hot extrusion further improved the distribution of CNTs. CNTs increased both the strength and elongation of the matrix alloy. Notably, the elongation of the matrix alloy was enhanced by 40%. Grain refinement and the pulling-out of CNTs resulted in the evident improvement of ductility for the composites.